Improving Energy Efficiency in Craiova, Romania - Mot, Manuela; Bose, Ranjan; Burduja, Sebastian; Ionescu-Heroiu, Marcel (World Bank, Washington, DC, 2016)
The main impetus for this report (and for the reports prepared for the other six growth poles) is a request received from the Ministry of Regional Development and Public Administration. The request came within the context of on-going preparations for the 2014-2020 Programming period, with Energy Efficiency being one the major themes of the Europe 2020 strategy, and a critical priority for all EU Member Countries. Within Romania, local authorities that will want to access energy efficiency funds under the 2014-2020 Regional Operational Program will need to first prepare energy efficiency strategies. The TRACE tool is specifically targeted at local authorities, and is a good instrument for drafting such strategies. After the 1989 Revolution, Romania began its transition from a centralized system to a market-based economy. Today the country is a member of the European Union (EU) and NATO. After more than a decade of economic restructuring and political change, the country has taken significant steps toward catching up with the economic performance of more developed EU countries. Although radical reforms brought about significant changes in recent years, the standard of living of Romanians is still behind the EU average. The transition period after the end of the communist regime has led to significant changes in the social and economic life of the residents of Craiova. Some of these developments have positively affected people's life, whereas a few came along with inconveniences and difficulties. During the first years of transition the city attracted people from parts of Dolj County and from elsewhere in Romania. This process led to severe de-population in the rural areas of Dolj County. At the same time, due to economic constraints, some of the urban population of Craiova moved to the wider metropolitan area. Like every other city in the country, municipal buildings in Craiova require proper measures toward improving energy efficiency - particularly in health care and education facilities managed by the city government. A benchmarking of the municipal building stock, along with audit and retrofit measures, should be performed in order to identify the highest energy savings potential and proper intervention measures. As for the water sector, although the system covers the entire city and most of the households in Craiova have water meters, there are high losses in the network. In addition, in order to improve the overall efficiency of the water system, oversized pumps needs to be replaced with smaller, energy-efficient ones. Finally, although selective collection has been implemented in Craiova, there is more that can be done about improving recycling rates.